2005
DOI: 10.1080/09553000500531886
|View full text |Cite
|
Sign up to set email alerts
|

Low dose radiation induced immunomodulation: Effect on macrophages and CD8+T cells

Abstract: LDR exposure enhanced the function of macrophages and responses of CD8(+) T cells in C57BL/6 mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 55 publications
(64 reference statements)
2
66
0
Order By: Relevance
“…Full body low dose radiation in mice has been found to enhance the function of macrophages (and CD8ϩ T cells) in several studies (18 -20). Current evidence suggests that the immune response is enhanced at lower doses and influences the production and the release of inflammatory cytokines and chemokines such as TNF-␣, IL-1␣, and others (18). The main goal of this study is to elucidate the mechanisms of the signal transmission for IR-induced radiobiological bystander responses in bone marrow-derived EPCs and determine the role of TNF ligand-receptor interaction in mediating RBR in these cells.…”
Section: Tnfr2/p75 Regulate Ir-induced Nontargeted Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full body low dose radiation in mice has been found to enhance the function of macrophages (and CD8ϩ T cells) in several studies (18 -20). Current evidence suggests that the immune response is enhanced at lower doses and influences the production and the release of inflammatory cytokines and chemokines such as TNF-␣, IL-1␣, and others (18). The main goal of this study is to elucidate the mechanisms of the signal transmission for IR-induced radiobiological bystander responses in bone marrow-derived EPCs and determine the role of TNF ligand-receptor interaction in mediating RBR in these cells.…”
Section: Tnfr2/p75 Regulate Ir-induced Nontargeted Effectsmentioning
confidence: 99%
“…Therefore, it is apparent that in addition to many factors that may influence bystander responses, including but not limited to production and release of inflammatory cytokines and chemokines, such as TNF-␣, IL-1␣, and others (9), there is a large intrinsic variability for bystander responses in different primary and tumor cells. Full body low dose radiation such as x-ray and ␥-IR has been found to induce apoptotic and immunological responses in various organ and tissues, including bone marrow (18). The acute phase is usually characterized by neutrophil infiltration of the affected area, whereas macrophages are responsible for the phagocytic clearance of the apoptotic cells (19,20).…”
Section: Radiation-induced Bystander Responses (Rbr)mentioning
confidence: 99%
See 1 more Smart Citation
“…LDR activates T cells, NK cells, and B cells, resulting in activation of the immune system and reduction in apoptotic cells induced by high dose radiation in healthy individuals [16][17][18]. At the molecular level, expression of key proteins involved in the process of apoptosis with LDR exposed human PBMCs is also being studied in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained from animal experiments demonstrated that low-dose whole-body irradiation enhanced the immune response by augmenting the proliferative reactive response of T cells to mitogenic stimulation (Kojima et al 2000a;Pandey et al 2005), altering cytokine release (Liu et al 2003;Cheda et al 2008) and immune cell populations (Ina and Sakai 2005), and/or augmenting T cell activation capacity by dendritic cells (Shigematsu et al 2007). Regarding autoimmunity, the potentiation of T cell-mediated immunity in autoimmune-prone mice following exposure to low-dose irradiation was examined at the end of the 20 th century (James and Makinodan 1988;James et al 1990), and several research groups subsequently focused on the effects of low-dose irradiation on autoimmune diseases such as systemic lupus erythematosus (Ootsuyama et al 2003;Tanaka et al 2005;Tago et al 2008), multiple sclerosis , rheumatoid arthritis (Nakatsukasa et al , 2010Weng et al 2010) and autoimmune thyroiditis (Nagayama et al 2008) after the start of the 21 st century.…”
Section: Introductionmentioning
confidence: 99%